Tough decisions : cases in medical ethics - Freeman, John Mark (Oxford University Press, 2001)
Life is full of tough decisions that must be made ethically and under the pressures of time. This book places readers in realistic situation where they experience the difficulties of making tough medical decisions. The cases are composites of actual cases the authors have seen or managed. In the role of decision-maker, the reader helps to determine what happens in the case as his or her decision often shapes the course of events and the patient's outcome. This gives a compelling sense of the pressures that bear on clinical decision-making. The authors assume that the reader wants to do the rig.
Keywords: Medical ethics -- Case studies.; Clinical medicine -- Decision making -- Case studies.; Decision making -- Moral and ethical aspects -- Case studies.; Decision making.; Medical ethics.; Bioethics.; Clinical medicine.; Human experimentation in medicine.; Adulthood.; Children.; Confidential communications.; Financial disclosure.; Do-not-resuscitate orders.; Genetic engineering.; Health care reform.; Informed consent (Medical law); Medical care.; Physician and patient.; Human reproductive technology.; Assisted suicide.; Decision Making; Ethics, Medical; Bioethical Issues; Bioethics; Patient Dropouts; Truth Disclosure; Clinical Medicine; Human Experimentation; Adult; Child; Confidentiality; Disclosure; Ethical Theory; Euthanasia, Passive; Genetic Engineering; Health Care Reform; Informed Consent; Patient Care; Physician-Patient Relations; Reproductive Techniques, Assisted; Resuscitation Orders; Suicide, Assisted; Éthique médicale -- Cas, Études de.; Médecine clinique -- Prise de décision -- Cas, Études de.; Prise de décision -- Aspect moral -- Cas, Études de.; Médecine clinique -- Prise de décision -- Études de cas.; Prise de décision -- Aspect moral -- Études de cas.; Prise de décision.; Éthique médicale.; Bioéthique.; Médecine clinique.; Expérimentation humaine en médecine.; Adultes.; Enfants.; Secret professionnel.; Divulgation financière.; Interruption de traitement.; Génie génétique.; Services de santé -- Réforme.; Consentement éclairé (Droit médical); Soins médicaux.; Relations médecin-patient.; Procréation médicalement assistée.; Aide au suicide.; Ordres de ne pas réanimer.; Abandon des soins par les patients.; decision making.; adults (people); adulthood.; children (people by age group); suicides.; MEDICAL -- Ethics.; Physician and patient; Medical care; Human reproductive technology; Human experimentation in medicine; Health care reform; Genetic engineering; Financial disclosure; Do-not-resuscitate orders; Decision making; Confidential communications; Clinical medicine; Children; Assisted suicide; Adulthood; Clinical medicine -- Decision making; Decision making -- Moral and ethical aspects; Medical ethics; Case Reports; Case studies; Case studies.; Études de cas.